Study on the Factors Influencing the Enrollment of Nanchang Vocational College under Educational Marketing - Ma, Li (International Journal of Sociologies and Anthropologies Science Reviews, 2023)
Background and Aim: This study aims to analyze the factors affecting the recruitment of students in private colleges and universities based on research data, analyzes the problems of recruitment in private colleges and universities and their causes, and then proposes recruitment management strategies based on educational marketing theory. Materials and Methods: NC Vocational College was selected as an example. A quantitative research approach was adopted to collect and analyze the data. Results: Results show that the former includes students’ motivation, family income, and parent’s education level, while the latter includes the school’s infrastructure conditions, teachers’ level, curriculum, and specialties. In addition, according to the actual situation of NC Vocational College, we analyze the disadvantages of its enrollment mode, insufficient quality of enrollment team, false or exaggerated enrollment propaganda, and confused enrollment incentive management and analyze the reasons for the problems of enrollment in private colleges and universities from the aspects of policy, school development mode, school quality, and employment. Lastly, this paper emphasizes that the enrollment work of private colleges and universities is "student-centered", market-oriented, and based on the demand for talents in society, and puts forward specific and constructive countermeasures in the aspects of enrollment organization planning, enrollment work team, enrollment work brand construction and enrollment work layout. Conclusions: It is hoped that this study will help NC Vocational College to optimize its recruitment mode and improve its recruitment management, to enhance the quantity and quality of recruitment, and also provide a reference for the recruitment management of other private universities in China.